[OP.1A.10] CONVENTIONAL AND AMBULATORY BLOOD PRESSURE AS PREDICTORS OF RETINAL ARTERIOLAR NARROWING. (September 2016) - Wei, F.; Zhang, Z.Y.; Thijs, L.; Yang, W.Y.; Jacobs, L.; Cauwenberghs, N.; Gu, Y.M.; Kuznetsova, T.; Allegaert, K.; Verhamme, P.; Li, Y.; Struijker-Boudier, H.A.J.; et al.
Abstract : Objective: To investigate to what extent conventional (CBP) and daytime ambulatory (ABP) blood pressure predict narrowing of the retinal microvasculature. Design and method: In a population-based longitudinal study, 783 white Flemish participants (mean age, 38.2 years; 51.3% women) were randomly recruited, whose blood pressure was measured at baseline and follow-up and who underwent retinal photography at follow-up. CBP and ABP were averaged of five consecutive auscultatory readings and ambulatory oscillometric readings (10 AM–8 PM) programmed at 20 minute intervals. Systolic/diastolic HT thresholds were 140/90 mmHg for CBP and 135/85 mmHg for ABP. Central retinal arteriolar (CRAE) and venular (CRVE) equivalents and their ratio (AVR) were used as retinal traits post-processed by Vasculomatic ala Nicola software. Results: In multivariable-adjusted models including both CBP and ABP at baseline, CRAE changes after 10.3 years (median) were unrelated to CBP (P >  = 0.14), whereas ABP predicted CRAE narrowing (P <  = 0.01). Per 1-SD increment in systolic/diastolic blood pressure, the association sizes were -0.95 μm (95% confidence interval, -2.20 to 0.30)/ -0.75 μm (-1.93 to 0.42) for CBP and -1.76 μm (-2.95 to -0.58)/-1.48 μm (-2.61 to -0.34) for ABP. CRVE was not related to CBP or ABP, while associations of AVR with blood pressure mirrored those of CRAE, the numerator of the ratio. In multivariable-adjusted models with baseline ABP and follow-up CBP, CRAE decreased (P <  = 0.049) by -1.61/-1.04 μm and by -2.60/-2.40 μm in relation to baseline daytime and follow-up conventional systolic/diastolic blood pressures, respectively. Compared with normotension (normal CBP and ABP; prevalence, 77.6%), HT patients had smaller CRAE (147.5 vs. 152.7 μm; P < 0.001) and AVR (0.68 vs. 0.70; P = 0.001). CRAE and AVR were not different (P >  = 0.06) between normotension and white-coat HT (elevated CBP and normal ABP; 5.4%) and between masked HT (normal CBP and elevated ABP; 10.2%) and HT (elevated CBP and ABP; 6.8%). Conclusions: The paradigm that retinal arterial narrowing precedes HT can be explained by the limitations of CBP measurement, including the nonidentification of masked HT.